PENGARUH STRUKTUR KEPEMILIKAN BANK DALAM PENGAMBILAN RISIKO BANK DI INDONESIA (RISK-TAKING) - Setyo Hartono (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
Another function of the bank is as a trust service in which the bank carries out money transfers. The function of banks illustrates that the existence of banks is important in a country's economy. Government ownership tends to be more difficult to reject government interference through decision making and policy, while privately owned banks tend to be more able to reject or oppose government policies that are expected to disrupt the running of the company. This research uses 3 (three) types of variables, namely, dependent, independent and control variables. The dependent variable in this research is the risk taking carried out by the bank, and the independent variable in this research is the bank ownership structure. Meanwhile, the control variables are bank size, bank efficiency, bank loan to deposits ratio (LDR), and bank capital adequacy ratio (CAR). regression test using a robustness check with the dependent variable bank risk taking (LnZscore) it can be concluded that the independent variable bank ownership structure (Ownership) has no significant effect on bank risk taking (LnZscore).